Pengaruh Ukuran Perusahaan, Leverage, Likuiditas, Perputaran Modal Kerja dan Pertumbuhan Penjualan Terhadap Profitabilitas (Sektor Industri Barang dan Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - ANGGARSARI, LOVI; SENO AJI, TONY (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to determine the effect of firm size, leverage, liquidity, working capital turnover and sales growth on profitability. sample company used is a company listed on the Indonesia Stock Exchange (IDX) period 2013 to 2016. Samples taken by using purposive sampling method so that 18 companies can be obtained as a sample. This study uses partial least square method (PLS) to determine the effect of firm size, leverage, liquidity, working capital turnover and sales growth on profitability (ROA). The result of this research show that firm size has an effect to profitability, leverage variable does not have an effect on profitability, liquidity variable does not effect to profitability, variable of working capital turnover does not effect to profitability and sales growth variable does not effect to profitability. so only the size of the company that has an effect on the profitability of companies in the sector of Goods and Consumption Industries listed in Indonesia Stock Exchange (IDX) period 2013-2016. Keywords: profitability, financial ratio, firm size